Akuntabilitas dan Transparansi Pengelolaan Alokasi Dana Desa (Studi Kasus Desa Cibiru Wetan) - Afifah Putri Salamah; Sri Utami; Sukamah S; Zahwa Dewi Yuningsari; Abdurachman A (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the implementation of accountability and transparency principles in the management of Village Fund Allocation (Alokasi Dana Desa/ADD) in Cibiru Wetan Village, Cileunyi District, Bandung Regency. The research employed a qualitative descriptive approach using document analysis based on secondary data, including the Village Revenue and Expenditure Budget (APBDes) Realization Reports for the 2020–2024 fiscal years published on the official website of Cibiru Wetan Village, supported by relevant laws, regulations, and academic literature. The analysis focused on the conformity of village financial management with the provisions of the Minister of Home Affairs Regulation Number 20 of 2018, the level of accountability, public transparency, and budget realization trends. The results indicate that the management of Village Fund Allocation in Cibiru Wetan Village has been implemented in accordance with the five stages of village financial management, namely planning, implementation, administration, reporting, and accountability. The principle of accountability is reflected in the consistently high average revenue realization of 98.58% and expenditure realization of 98.11% during the 2020–2024 period, as well as the consistent reporting of the Budget Surplus (SiLPA). Transparency has been realized through the periodic publication of APBDes realization reports on the village's official website, allowing the public to access financial information openly. Trend analysis also reveals positive growth in both village revenue and expenditure, with a consistent annual budget surplus resulting in an accumulated SiLPA of approximately IDR 3.79 billion over the five-year period. However, transparency remains largely one-way, and budget absorption has not yet been fully optimized.